2016
DOI: 10.1097/phm.0000000000000453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hospital Length of Stay on Functional Independence Measure Score in Trauma Patients

Abstract: An increased ratio of HLOS/RLOS increases the risk of LFIM more than 2-fold after adjusting for injury severity score, spinal cord injury, and FIM upon RF admission. Delays in transfer to an RF negatively affect patient functional outcomes. Studies to identify factors affecting delays in transfer from hospitals to RF should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…The author have been observed that there is negative correlation of LOSa with FIMd and Gain (r=-0.507, p=0.00 and r=-0.402, p=0.004), respectively. Similarly, Muakkassa et al [14] published that an increased risk of low FIM (OR, 2.21; 95% CI, 1.41-3.45; P=0.001) was observed with an increased ratio of Hospital length of Stay (HLOS/RLOS) after adjusting for injury severity score. FIMa is positively correlated with FIMd but negatively correlated to gain.…”
Section: Resultsmentioning
confidence: 84%
“…The author have been observed that there is negative correlation of LOSa with FIMd and Gain (r=-0.507, p=0.00 and r=-0.402, p=0.004), respectively. Similarly, Muakkassa et al [14] published that an increased risk of low FIM (OR, 2.21; 95% CI, 1.41-3.45; P=0.001) was observed with an increased ratio of Hospital length of Stay (HLOS/RLOS) after adjusting for injury severity score. FIMa is positively correlated with FIMd but negatively correlated to gain.…”
Section: Resultsmentioning
confidence: 84%
“…Frailty due to aging may have also impacted recovery and increased the risk of complications in our population, as frailty has been shown to negatively impact health outcomes by 2-5 times (15,36,37,39). Comprehensive geriatric assessment and tailored treatment approaches are essential for optimizing outcomes in older adult trauma patients given they already have delays in reaching care, stay longer in hospitals following injuries, and are more likely to die compared to younger adults (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Um doente que se mantém durante mais tempo em meio hospitalar encontra-se necessariamente fora da sua rotina, torna-se mais sedentário e recebe menor estímulo à função e autonomia. 22,23 Estes achados parecem ser independentes do grau de complexidade ou severidade do diagnóstico de entrada e da sua progressão clínica. 22,23 Esta é também a principal justificação para a crescente necessidade de incluir no plano de alta hospitalar a intervenção dos profissionais de reabilitação nestes doentes, o que se refletiria de forma positiva na sua independência e na redução de complicações secundárias, tais como quedas ou delirium.…”
Section: Discussionunclassified
“…22,23 Estes achados parecem ser independentes do grau de complexidade ou severidade do diagnóstico de entrada e da sua progressão clínica. 22,23 Esta é também a principal justificação para a crescente necessidade de incluir no plano de alta hospitalar a intervenção dos profissionais de reabilitação nestes doentes, o que se refletiria de forma positiva na sua independência e na redução de complicações secundárias, tais como quedas ou delirium. 24,25 A prorrogação de uma alta hospitalar tem um impacto negativo não só no utente -num momento de particular vulnerabilidade e exposição a potenciais reinfeções e agravamento da sua condição de saúde e independência -mas também na gestão hospitalar, tanto logística como economicamente.…”
Section: Discussionunclassified